The vulnerables in the COVID-19 period: an integrative literature review (Research, Society and Development, 2020)
A new, deadly and unknown virus, originating from the bat, emerged in late 2019 in Wuhan, China, spreading across continents, known as the COVID-19  pandemic, challeging social, economic and health politics. Objective: Investigate who are vulnerable to COVID-19 pandemic in Brazil and the World. Methodology: An integrative literature review of an exploratory nature was applied, analyzing articles published in the year 2020 that addressed the theme “Coronavírus” and “vulnerable people” Using the Mesh: “coronavirus”, ‘Covid-19” and “Epidemic”.Results and discussion: Scielo, BIREME e  Pubmed databases were used. In the inicial search, 155 articles were found, after the filter 20 studies remained and that at the end, 12 articles were used as the basis of this article. Conclusion: In this review, we observed that the risk of dying from Covid-19 increases with age, but it isn’t the main determining factor, since in Brazil the Scenario has been different from what occurred in other initial countries of the pandemic.